On the Relationship between High School Students’ Stress and their Use of Computer & Purpose of Using Internet - Han, Mi Hee (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: The current research aims to identify the relationship between high school students’ use of computer/smartphones and their stress.